The Economic Determinants of Mystical Healing: An Empirical Exploration of Danyalism in the Sociocultural Landscape of Gilgit Baltistan - Faiz, Farhan Ahmad; Sadaf, Fouzia; Ahmed, Farrah; Parveen, Amna (iRASD Journal of Economics, 2023)
Danyalism, a spiritual healing system prevalent in the Hunza and Nagar valleys of Gilgit Baltistan, represents a syncretic fusion of the mystical and the corporeal. The Danyal, the practitioner at the center of this complex sociocultural system, is imbued with an ethereal connection to the Faerie realm, possessing an authoritative power to remedy sickness through esoteric rites. From an economic perspective, the study also explores the cost-efficiency and accessibility of danyalistic healing, examining how these practices fit within the broader healthcare economy of the region. The empirical exploration undertaken in this study utilized a robust methodological framework, encompassing both survey and case study techniques. A total of 100 female respondents were surveyed for quantitative analysis, selected via snowball sampling, and 4 Danyals were interviewed for qualitative insights, selected through convenient sampling. Employing structured, closed-ended questionnaires and interview guides facilitated the gathering of nuanced qualitative and quantitative data. The results revealed a profound, albeit covert, adherence to danyalistic healing practices among female respondents. Despite existing within a cultural matrix where engaging with a Danyal is stigmatized as a social taboo, a substantial proportion of the population opts for this traditional healing method over conventional medical care, influenced by factors such as affordability and cultural acceptance. The findings illuminate the intricate interplay between belief systems, cultural norms, economic considerations, and health-seeking behaviors in the region, revealing the persistent resonance of danyalistic practices, even in the face of societal prohibition. The economic implications of this study further broaden our understanding of the healthcare choices made by individuals within a specific sociocultural and economic context.